2016
DOI: 10.1155/2016/4316424
|View full text |Cite
|
Sign up to set email alerts
|

Development of Flexible Polyurethane Nanostructured Biocomposite Foams Derived from Palm Olein-Based Polyol

Abstract: This study examined the effect of organoclay montmorillonite (OMMT) on the mechanical properties and morphology of flexible polyurethane/OMMT nanocomposite (PU/OMMT) foams prepared from petroleum- and palm olein-based polyols. Palm-based PU foams exhibited inferior mechanical strength as compared to neat petroleum PU foams. However, addition of OMMT significantly improved the foams strength of flexible polyurethane/OMMT nanocomposite foams prepared from palm olein-based polyol (PU bionanocomposite foam). The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 51 publications
(62 reference statements)
1
8
0
Order By: Relevance
“…Moreover, the possible interphase interactions between POSS and PU in cell struts disturbed formulation of stable foam structure [27] which results in the coalescence of crowded cells. The alteration of cell morphology as the result of filler incorporation was also observed in previous studies [28,35,55].…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Moreover, the possible interphase interactions between POSS and PU in cell struts disturbed formulation of stable foam structure [27] which results in the coalescence of crowded cells. The alteration of cell morphology as the result of filler incorporation was also observed in previous studies [28,35,55].…”
Section: Resultssupporting
confidence: 83%
“…It was reported that, in addition to traditional fillers, an interesting group of reactive nanofillers are polyhedral oligomeric silsesquioxanes (POSS), which combine the features of organic and inorganic materials [29,30,31]. They were discovered at the beginning of the 20th century and are currently in the interest of many research centers due to their unique properties, including well-defined, three-dimensional, chemically and thermally resistant hybrid structure with nanoscopic dimensions [32,33,34,35]. Their biggest advantage is the ease of functioning with various organic or inorganic substituents.…”
Section: Introductionmentioning
confidence: 99%
“…The formation of polyurethane foams has been studied extensively with same general reaction of isocyanate with polyol. 32 In general, the reaction demonstrates the fundamental group of the polyurethane polymer including urethane and urea linkages, uretoneimine ring structure and unreacted isocyanate. Identification of functional groups of commercial and palm-based RPUFs are demonstrated in Figure 4.…”
Section: Resultsmentioning
confidence: 93%
“…[15][16][17][18][19][20][21][22] Moreover, partial replacement of petroleum-based polyols with biobased polyols is an alternative approach for the preparation of polyurethane for applications such as coatings, adhesives, sealant, elastomer, as well as flexible and rigid foams. [23][24][25][26][27][28][29][30][31][32][33][34][35] The possibility of utilising castor oil and crude glycerol to produce bio-based polyols and subsequently RPUFs was explored by Carrico et al 5 Different amounts and types of blowing agent (water, pentane and cyclo-pentane) and catalyst (DBTDL) were examined in the study. Increase amount of water content resulted in a decrease in density, thermal conductivity, compressive strength and Young's modulus.…”
Section: Introductionmentioning
confidence: 99%
“…This may result in poor interfacial adhesion between the filler surface and the PUR matrix, which promotes earlier cell collapsing phenomena and increases a high possibility of generating open pores [50]. Deterioration of the foam morphology after the incorporation of the filler was reported in previous studies as well [51][52][53].…”
Section: Characterization Of Pur Composites Reinforced With Walnut Shell Fillersmentioning
confidence: 85%